2003
DOI: 10.1182/blood.v101.6.2401
|View full text |Cite
|
Sign up to set email alerts
|

Stroke risk in siblings with sickle cell anemia

Abstract: Cerebrovascular disease is a common cause of morbidity in sickle cell anemia (HbSS): approximately 10% of patients have a clinical stroke before 20 years of age, and another 22% have silent infarction on magnetic resonance imaging. The phenotypic variation among patients with HbSS suggests a role for modifier genes and/or environmental influences. To assess the familial component of clinical stroke in HbSS, we estimated the prevalence of clinical stroke among all patients and among HbSS sibling pairs at 9 pedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(54 citation statements)
references
References 46 publications
(30 reference statements)
2
51
0
1
Order By: Relevance
“…11 TCD results indicating risk, 12 such as stroke, 13 have been reported to cluster among siblings. The STOP study is the largest prospective application of TCD (or any testing modality) for stroke prediction yet reported, and the screening and follow-up studies of STOP provide a unique opportunity to further the knowledge of TCD as a predictor for stroke in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…11 TCD results indicating risk, 12 such as stroke, 13 have been reported to cluster among siblings. The STOP study is the largest prospective application of TCD (or any testing modality) for stroke prediction yet reported, and the screening and follow-up studies of STOP provide a unique opportunity to further the knowledge of TCD as a predictor for stroke in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…Two of the strokes described above occurred in twin siblings, a few months apart. It has been previously reported that abnormal TCD measurements and stroke are more common in children with SCA, who have a sibling with SCA and either abnormal TCD velocities or prior stroke [12,13]. Earlier TCD screening should be considered for siblings with SCA if there is a family history of sickle-related cerebrovasculopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Advocating for studies on genomics of cardiovascular diseases in SCD Familial studies have provided evidence that predisposition to specific phenotypes of SCD such as stroke can be genetically inherited (Driscoll et al, 2003). However, there is limited evidence on the genetic polymorphisms influencing the vast clinical heterogeneity and disease severity across populations, with very few studies particularly in Africa.…”
Section: Discussionmentioning
confidence: 99%
“…Underlying genetic contributions to stroke risk in SCD patients have been identified through sibling pair, epidemiologic, and animal model studies (Driscoll et al, 1997(Driscoll et al, , 2003. The alpha-thalassemia polymorphism, a 3.7 or 4.2 kb deletion (Flanagan et al, …”
Section: Stroke In Scdmentioning
confidence: 99%